Education on Making Floor Cleaning Soap from Used Cooking Oil (SUPERMIJEL) - Rahma Diyan Martha; Fatimah Fatimah; Nurul Chamidah Kumalasari; Wimbuh Tri Widodo; Danar Danar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Waste cooking oil is also called used oil used for frying. The use of used cooking oil can have an impact onour bodies, and indiscriminate disposal of the waste can pollute the environment and waters. So, there needsto bea smart solution to overcome this problem. This community service activity aims to socialize thedangers of used cooking oil and provide knowledge about other benefits of used cooking oil. The method used in this activity is the delivery of materials and direct practice of making products. The evaluation of thisactivity can be seen from the questionnaires distributed before and after theactivity started. The results of the evaluation activities were an increase in knowledge about the dangers of using cooking oil repeatedly for health. In addition, residents gained new knowledge and direct practice about other benefits of usedcooking oil, namely, floor cleaning soap from usedcooking oil. This community service activity can be followedby the participants well and with highenthusiasm